Environmental Toxicity Assessment of Organotin Compounds Using the Direct Contact Bioassay – OSTRACODTOXKIT F - Tomasz Szwarc; Piotr Komasara; Paweł Mikołajczak; Mateusz Kałwik; Mateusz Michalak; Hubert Bochenek; Julia Nowakowska; Iga Klepacz (Journal of Education, Health and Sport)
The aim of the study was to assess the toxicity of organic compound of tin using two tests with Heterocypris incongruens.